Cross‐linked hemoglobin bis‐tetramers from bioorthogonal coupling do not induce vasoconstriction in the circulation. Issue 1 (15th November 2018) - Wang, Aizhou; Singh, Serena; Yu, Binglan; Bloch, Donald B.; Zapol, Warren M.; Kluger, Ronald
Abstract : BACKGROUND: Hemoglobin‐based oxygen carriers (HBOCs) are potential alternatives to red blood cells in transfusions. Clinical trials using early versions of HBOCs noted adverse effects that appeared to result from removal of the vasodilator nitric oxide (NO). Previous reports suggest that size‐enlarged HBOCs may avoid NO‐rich regions along the vasculature and therefore not cause vasoconstriction and hypertension. STUDY DESIGN AND METHODS: Hemoglobin (Hb) bis‐tetramers (bis‐tetramers of hemoglobin that are prepared using CuAAC chemistry [BT‐Hb] and bis‐tetramers of hemoglobin that are specifically acetylated and prepared using CuAAC chemistry [BT‐acHb]) can be reliably produced by a bio‐orthogonal cyclo‐addition approach. We considered that an HBOC derived from chemical coupling of two Hbs would be sufficiently large to avoid NO scavenging and related side effects. The ability of intravenously infused BT‐Hb and BT‐acHb to remain in the circulation without causing hypertension were determined in wild‐type (WT) and diabetic ( db/db ) mouse models. RESULTS: In WT mice, the coupled oxygen‐carrying proteins retained their function over several hours after administration. No significant changes in systolic blood pressure from baseline were observed after intravenous infusion of BT‐Hb or BT‐acHb in awake WT and db/db mice. In contrast, infusion of native Hb or cross‐linked Hb tetramers in both animal models induced systemic hypertension. CONCLUSION: The results of this study indicate that bis‐tetrameric HBOCs derived from the bio‐orthogonal cyclo‐addition process are likely to overcome clinical issues that arise from NO scavenging by Hb derivatives.